XXIII Balcanicum, Cultural Borderlands in Southeastern Europe, Poznan, October 25-26th, 2024 - conference report - Sajkowski, Wojciech (Balcanica Posnaniensia. Acta et studia, 2024)
The XXIII Balcanicum conference, organised by the Balkan Studies Commission, in cooperation with the Faculty of History of the Adam Mickiewicz University, was held on 25-26 October 2024. The conference XXIII Balcanicum, organised by the Balkan Studies Commission, in cooperation with the Faculty of History of the Adam Mickiewicz University, was held on 25-26 October 2024. The theme of this year's scientific session was formulated as follows: Sites of Memory and Historical Politics in Southeastern Europe. During the conference, 28 papers were presented by researchers from Polish and foreign centres (7), mainly in the form of stationary. The topic of cultural borderlands was analysed by the authors of the papers in an extremely broad way. Among the presentations, there was no shortage of analyses devoted to the impact of cultural borderlands on the functioning of states, national, regional and local communities, families and individuals.